Grecia e Turchia in competizione nel Mediterraneo orientale: il caso emblematico di Cipro - Delvecchio, Anna Maria (Cultura giuridica e diritto vivente, 2020)
[Greece and Turkey competing in the eastern Mediterranean: the emblematic case of Cyprus] The geographical position, the presence of different ethnic groups, Greeks, Turks, and others, has led to a continuous claim on the dominion of the island, a crossroads in the eastern Mediterranean, by external powers. The proclaimed independence did not resolve the ethnic conflicts to the point of creating a division of the territory.